OPTIMIZATION OF GROUND PHOTOMETRIC METHOD OF MEASUREMENT OF VEGETATION LEAF AREA INDEX - Fakhraddin G. Agaev; Meraj E. Omarov (Измерение, мониторинг, управление, контроль, 2024)
Background. In the article, the problem of optimizing ground measurements of the sheet area index was formed taking into account the change in the Solz zenith angle during sunrise and approach in the opposite order. Materials and methods. A mid-integral modification of the LAI index in the form of some functionality is proposed. Results and conclusions. It is determined that the proposed functionality, taking into account the introduced limiting condition, has extremals in the form of functional dependencies of incoming optical radiation and optical radiation passing through the vegetation crown from the zenith angle of the Sun. It is shown that the first of these extremals provides the maximum target functionality and the second minimum.